Planning the Size of Clinical Trials with Allowance for Patient Noncompliance - Moussa, M. A. A. (Methods of Information in Medicine, 1990)
Various approaches are considered for adjustment of clinical trial size for patient noncompliance. Such approaches either model the effect of noncompliance through comparison of two survival distributions or two simple proportions. Models that allow for variation of noncompliance and event rates between time intervals are also considered. The approach that models the noncompliance adjustment on the basis of survival functions is conservative and hence requires larger sample size. The model to be selected for noncompliance adjustment depends upon available estimates of noncompliance and event rate patterns.
Keywords: Clinical Trial; Sample Size; Noncompliance; Survival Analysis; Proportions